A matched comparison study of hepatitis C treatment outcomes in the prison and community setting, and an analysis of the impact of prison release or transfer during therapy. Issue 12 (11th August 2016) - Aspinall, E. J.; Mitchell, W.; Schofield, J.; Cairns, A.; Lamond, S.; Bramley, P.; Peters, S. E.; Valerio, H.; Tomnay, J.; Goldberg, D. J.; Mills, P. R.; Barclay, S. T.; et al.
Summary: Prisoners are a priority group for hepatitis C (HCV) treatment. Although treatment durations will become shorter using directly acting antivirals (DAAs), nearly half of prison sentences in Scotland are too short to allow completion of DAA therapy prior to release. The purpose of this study was to compare treatment outcomes between prison‐ and community‐based patients and to examine the impact of prison release or transfer during therapy. A national database was used to compare treatment outcomes between prison treatment initiates and a matched community sample. Additional data were collected to investigate the impact of release or transfer on treatment outcomes. Treatment‐naïve patients infected with genotype 1/2/3/4 and treated between 2009 and 2012 were eligible for inclusion. 291 prison initiates were matched with 1137 community initiates: SVRs were 61% (95% CI 55%–66%) and 63% (95% CI 60%–66%), respectively. Odds of achieving a SVR were not significantly associated with prisoner status ( P =.33). SVRs were 74% (95% CI 65%–81%), 59% (95% CI 42%–75%) and 45% (95% CI 29%–62%) among those not released or transferred, transferred during treatment, or released during treatment, respectively. Odds of achieving a SVR were significantly associated with release ( P <.01), but not transfer ( P =.18). Prison‐based HCV treatment achieves similar outcomes to community‐based treatment, with those not released or transferred during treatment doing particularly well. Transfer or release during therapy should be avoided whenever possible, using anticipatory planning and medical holds where appropriate.